Higher prevalence of joint hypermobility in constipation predominant irritable bowel syndrome. Issue 9 (23rd April 2018) - Zweig, A.; Schindler, V.; Becker, A. S.; van Maren, A.; Pohl, D.
Abstract: Background: Joint hypermobility syndrome (JHS) is characterized by excessive connective tissue laxity manifest as joint hypermobility (JH) together with musculoskeletal symptoms. Previous studies have shown an association between JH/JHS and gastrointestinal symptoms, including irritable bowel syndrome (IBS), although its association with specific IBS subtypes is incompletely understood. We aimed to determine the prevalence of JH according to the subtypes of IBS, in particular IBS‐C and IBS‐D. Methods: Data of 228 consecutive IBS patients were analyzed. IBS was subtyped into constipation and diarrhea predominant IBS (IBS‐C and IBS‐D), IBS with mixed bowel habits (IBS‐M) and unsubtyped IBS (IBS‐U). JH was defined as a Beighton Score ≥4/9 points and JHS diagnosed according to revised Brighton Criteria. Data of IBS patients were analyzed for psychological comorbidities assessed by Hospital Anxiety and Depression Scale (HADS) and Visceral Sensitivity Index (VSI). Key Results: Of 228 IBS patients, 64 (28.1%) suffered from IBS‐C, 89 (39.0%) from IBS‐D, 48 (21.1%) from IBS‐M, and 27 (11.8%) from IBS‐U. JH was diagnosed in 95 patients (41.7%). The prevalence of JH was significantly higher in IBS‐C than IBS‐D (57.8% vs 34.8%, P = .031). There was no significant difference in VSI and HADS according to JH or IBS subtype. Conclusions and Interferences: The prevalence of JH was significantly higher in IBS‐C compared to IBS‐D. Abnormalities in the connective tissue biomechanics in those with JH may contribute to a degree of colonic inertia which could result in constipation in JH‐positive IBS patients. Further work is needed to determine the colonic biomechanics in patients with JH. Abstract : The role of joint hypermobility (JH) in functional gastrointestinal disorders (in particular in irritable bowel syndrome [IBS]) and the exact underlying pathophysiology have been incompletely understood so far. We could now demonstrate a significantly higher prevalence of JH in IBS‐C than IBS‐D. This led to the assumption that IBS‐C and IBS‐D constitute 2 different entities partially associated with connective tissue disorders and therefore represent a next step to reveal the pathogenesis of IBS‐C.